Two Circles?

Algebra Level 5

If ( x 5 ) 2 + ( y 4 ) 2 = 3 2 (x-5)^2 + (y-4)^2 = 3^2 , maximize ( x 4 ) 2 + ( y 5 ) 2 (x-4)^2 + (y-5)^2 .


The answer is 19.485.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Cody Johnson
Sep 14, 2014

Without any algebra, notice that the first is a circle centered at ( 5 , 4 ) (5,4) and radius 3 3 . Then we want to find the largest radius of a circle centered at ( 4 , 5 ) (4,5) that touches the other circle. With this geometric interpretation, it's easy to see that this occurs on the line connecting the two centers of the circles. In terms of coordinates, this occurs where y = 9 x y=9-x , which quickly gives the point ( 10 + 3 2 2 , 8 3 2 2 ) \left(\frac{10+3\sqrt2}2,\frac{8-3\sqrt2}2\right) .

Aditya Raut
Sep 13, 2014

Solution 1 -We have

( x 4 ) 2 + ( y 5 ) 2 = ( x 5 ) 2 + ( y 4 ) 2 + 2 x 2 y = 9 + 2 ( x y ) (x-4)^2+(y-5)^2=(x-5)^2+(y-4)^2+2x-2y=9+2(x-y) .... So we actually want to maximize x y x-y .

We'll use substitution,

( y 4 ) 2 = 3 2 ( x 5 ) 2 = ( 3 + x 5 ) ( 3 x + 5 ) = ( x 2 ) ( x 8 ) y 4 = x 2 + 10 x 16 y = x 2 + 10 x 16 + 4 (y-4)^2=3^2-(x-5)^2 = (3+x-5)(3-x+5)=-(x-2)(x-8)\\ \therefore y-4=\sqrt{-x^2+10x-16} \implies y =\sqrt{-x^2+10x-16}+4

Maximize x x 2 + 10 x 16 4 x-\sqrt{-x^2+10x-16}-4 , thus d ( x x 2 + 10 x 16 4 ) d x = 0 1 2 x + 10 2 x 2 + 10 x 16 = 0 x 5 x 2 + 10 x 16 = 1 ( x 5 ) 2 = x 2 + 10 x 25 2 x 2 20 x + 41 = 0 \dfrac{d(x-\sqrt{-x^2+10x-16}-4)}{dx}=0 \implies 1-\dfrac{-2x+10}{2\sqrt{-x^2+10x-16}}=0 \\ \implies \dfrac{x-5}{\sqrt{-x^2+10x-16}}=-1 \\ \therefore (x-5)^2=-x^2+10x-25 \implies 2x^2-20x+41=0

(further part of this is in solution 2)


Solution 2- the wanted expression is

( x 4 ) 4 + ( y 5 ) 2 = x 2 8 x + 16 + ( x 2 + 10 x 16 1 ) 2 = x 2 8 x + 16 x 2 + 10 x 16 + 1 2 x 2 + 10 x 16 = 2 x 2 + 10 x 16 + 2 x + 1 (x-4)^4+(y-5)^2 \\ = x^2-8x+16 + (\sqrt{-x^2+10x-16}-1)^2 \\ =x^2-8x+16 -x^2+10x-16 +1 -2\sqrt{-x^2+10x-16} \\ = 2\sqrt{-x^2+10x-16} +2x+1


This is maximum at d ( 2 x 2 + 10 x 16 + 2 x + 1 ) d x = 0 \dfrac{d(2\sqrt{-x^2+10x-16} +2x+1)}{dx} =0


Thus 2 2 x + 10 2 x 2 + 10 x 16 + 2 = 0 2 x 2 + 10 x 16 = 2 x + 10 x 2 + 10 x 16 = ( x 5 ) 2 = x 2 10 x + 25 2 x 2 20 x + 41 = 0 2 x 2 20 x + 32 = 9 x 2 10 x + 16 = 9 2 2\dfrac{-2x+10}{2\sqrt{-x^2+10x-16}}+2=0 \\ \therefore 2\sqrt{-x^2+10x-16}= -2x+10 \\ \therefore -x^2+10x-16=(x-5)^2=x^2-10x+25 \implies 2x^2-20x+41=0 \\ \therefore 2x^2-20x+32=-9 \implies x^2-10x+16=\dfrac{-9}{2}


And, larger solution of x x from this quadratic is 20 + 400 4 × 2 × 41 4 = 5 + 3 2 2 \dfrac{20+\sqrt{400-4\times 2 \times 41}}{4} = 5 + \dfrac{3\sqrt{2}}{2}


Put these values in required equation to get

m a x ( x 4 ) 2 + ( y 5 ) 2 = 2 9 2 + 10 + 3 2 + 1 = 11 + 6 2 19.485 max(x-4)^2+(y-5)^2 = 2\sqrt{\dfrac{9}{2} } + 10 + 3 \sqrt{2} +1 = 11 + 6\sqrt{2} \approx \boxed{19.485}

Aditya, could you think of a shorter solution that uses not Calculus ?

Guilherme Dela Corte - 6 years, 9 months ago
Atomsky Jahid
Jun 11, 2016

The distance between (5, 4) and (4, 5) is 2 \sqrt{2} . So, the distance between the points on the circle (determined by the equation) and (4, 5) can have values between 3 + 2 3+\sqrt{2} and 3 2 3-\sqrt{2} . Our goal is to maximize the distance squared which is ( 3 + 2 ) 2 = 11 + 6 2 (3+\sqrt{2})^2=11+6\sqrt{2} .

Kenny Lau
Sep 16, 2014

This question is the same as "if (x,y) is 3 units away from (5,4), what is its maximum distance from (4,5)".

Draw it on a Cartesian plane and you'll get 3 + 2 3+\sqrt2 units, and the answer is it squared.

With the substitution x = 3 sin x + 5 x = 3 \sin{x} + 5 and y = 3 cos x + 4 y = 3 \cos{x} + 4 , we see that the initial equation is satisfied. The one we want to maximize can be rewritten as ( 3 sin x + 1 ) 2 + ( 3 cos x 1 ) 2 = 9 ( sin 2 x + cos 2 x ) + 6 ( sin x cos x ) + 2 (3 \sin{x} + 1)^2 + (3 \cos{x} - 1)^2 = 9(\sin^2 {x} + \cos^2 {x}) + 6(\sin{x} - \cos{x}) + 2 = 11 + 6 ( sin x + cos x ) = 11 + 6 (\sin{x} + \cos{x}) .

Factoring sin x + cos x \sin{x} + \cos{x} to 2 ( 2 2 sin x + 2 2 cos x ) \sqrt{2} ( \frac{\sqrt{2}}{2} \cdot \sin{x} + \frac{\sqrt{2}}{2} \cdot \cos{x}) , we see that it equals 2 sin ( x + π 4 ) \sqrt{2} \cdot \sin{(x+\frac{\pi}{4})} , and its maximum is obviously 2 \sqrt{2} .

So our desired value of 11 + 6 ( sin x + cos x ) = ( x 4 ) 2 + ( y 5 ) 2 11 + 6 (\sin{x} + \cos{x} )= (x-4)^2 + (y-5)^2 is 11 + 6 2 19.485. 11 + 6 \sqrt{2} \approx \boxed{19.485.}

@Aditya Raut , check this out!

Guilherme Dela Corte - 6 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...